A multidisciplinary study of ecosystem evolution through early Pleistocene climate change from the marine Arda River section, Italy. Issue 2 (March 2018) - Crippa, Gaia; Baucon, Andrea; Felletti, Fabrizio; Raineri, Gianluca; Scarponi, Daniele
Abstract: The Arda River marine succession (Italy) is an excellent site to apply an integrated approach to paleoenvironmental reconstructions, combining the results of sedimentology, body fossil paleontology, and ichnology to unravel the sedimentary evolution of a complex marine setting in the frame of early Pleistocene climate change and tectonic activity. The succession represents a subaqueous extension of a fluvial system, originated during phases of advance of fan deltas affected by high-density flows triggered by river floods, and overlain by continental conglomerates, indicating a relative sea level fall and the establishment of a continental environment. An overall regressive trend is observed through the section, from prodelta to delta front and intertidal settings. The hydrodynamic energy and the sedimentation rate are not constant through the section, but they are influenced by hyperpycnal flows, whose sediments were mainly supplied by an increase in Apennine uplift and erosion, especially after 1.80 Ma. The Arda section documents the same evolutionary history of coeval successions in the Paleo-Adriatic region, as well as the climatic changes of the early Pleistocene. The different approaches used complement quite well one another, giving strength and robustness to the obtained results.